Islamic College and Local Culture: Internalization and Integration - Puspita, Fulan; Lessy, Zulkipli (EDUKASIA, 2021)
This study aims to determine Indonesian Islamic values' integration and internalization in building students’ personalities as teacher candidates. The research method used is a qualitative phenomenological approach. The data source comes from the head of FTIK Salatiga State Institute for Islamic Studies (IAIN), five lecturers, and 25 students. The study concludes: (1) stage of value transaction is conducted in every college activity either inside the class or in the campus environment by considering laws, social regulations, and obligations attached to every student in preparing them to return serving the community and state as well as religion. (2) Stage of the social contract. In this stage, the student has acted by considering that they have certain obligations toward society and certain obligations to them. (3) Trans-internalization stage; students have found values, and they regard them as universal values that influence an individual’s character. In all the steps, the more measures developed will be instilled within the student to take a strong effort and relatively-long enough time to reach the desired outcome.